Glucagon-like peptide-1 receptor agonists for treatment of diabetes and obesity: advantage of oral delivery - New, R. R. C.; Bogus, M.; Travers, G. N.; Hahn, U.; Vaiceliunaite, A.; Burnet, M.; Wang, J. H.; Wen, H. (Frontiers in Drug Delivery, 2024)
GLP-1 receptor agonists ((GLP-1 RAs) are currently receiving a lot of attention because of their impact in diabetes, weight loss and other areas. While GLP-1 RAs in injectable form are highly efficacious, further work is required to develop oral versions which can deliver these peptides efficiently without requiring use of excessively high doses. This paper describes the ability of an oral peptide delivery formulation, Axcess™, to enhance uptake of GLP-1 receptor agonists via the intestine, resulting in changes in insulin and glucose blood levels indicative of biopotencies of 9% for exendin-4 and 14.8% for semaglutide in preclinical models. The route of delivery suggests that the peptides will be able to interact with the GLP-1 receptors on the vagal afferents of the intestine, as is the case for native GLP-1 in healthy individuals. GLP-1 receptor agonists administered via this route will be a valuable addition to the therapeutic modalities available for treatment of diabetes and obesity.